Development of indazole mineralocorticoid receptor antagonists and investigation into their selective late-stage functionalization. Issue 14 (15th July 2019) - Liu, Kun; Kurukulasuriya, Ravi; Dykstra, Kevin; DiMichelle, Lisa; Liu, Jinchu; Vachal, Petr; Ogawa, Anthony; DeVita, Robert J.; Shen, Dong-Ming; Tan, Qiang; Chen, Yili; Gauthier, Don; et al.
Graphical abstract: Abstract: The derivatization of pharmaceuticals is a core activity in the discovery and development of new medicines. Late-stage functionalization via modern CH functionalization chemistry has emerged as a powerful technique with which to diversify advanced pharmaceutical intermediates. We report herein a case study in late-stage functionalization towards the development of a new class of indazole-based mineralocorticoid receptor antagonists (MRA). An effort to modify the electronics of the core indazole heterocycle inspired the use of modern CH borylation chemistry. New reactivity patterns were revealed and studied computationally. Ultimately, a de novo synthesis delivered a key 6-fluoroindazole compound 26, a potent MRA with excellent metabolic stability.